The circumstances of post-phenomenological life worlds - Mccormack, D (Wiley, 2016)
This paper contributes to the development of a post-phenomenological account of world through a discussion of the concept of circumstance. This account is developed initially through a consideration of how the concept of world figures in two important strands of contemporary thinking, namely, speculative realism and theories of affective life. By making connections across these approaches, the paper argues for a circumstantial sense of worlds irreducible to the status of surrounds for human-centred forms of life and experience. This account of worlds is post-phenomenological insofar as it does not assume the already constituted subject as the condition for worlds to take shape: instead, it attends to the circumstantial worlding of forces excessive of the subject. At the same, via a scenographic orientation it remains attentive to the affective force of life worlds, to how they are felt as a kind of circumstantial palpability.